2014
DOI: 10.1111/1467-8268.12086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Real Exchange Rate on Trade Balance in Nigeria

Abstract: The study investigated whether the depreciation of exchange rate has a favourable impact on trade balance in Nigeria, based on the Marshall-Lerner (ML) condition. The Johansen method of cointegration and vector error correction methodology (VECM) was employed to investigate the existence of a long-run relationship between trade balance and the specified set of independent variables. The results confirm the satisfaction of the Marshall-Lerner condition in Nigeria, implying that depreciation of the exchange rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…With regard to Nigeria, which is the present case of analysis, a number of studies recently undertaken on the impact of currency devaluation (depreciation) seem to find mixed results (see, for instance, Ogundipe et al ., ; Iyoboyi and Muftau, ; Igue and Ogunleye, ; Aliyu and Tijjani, ; Akinlo and Lawal, ). Ogundipe et al .…”
Section: Empirical Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…With regard to Nigeria, which is the present case of analysis, a number of studies recently undertaken on the impact of currency devaluation (depreciation) seem to find mixed results (see, for instance, Ogundipe et al ., ; Iyoboyi and Muftau, ; Igue and Ogunleye, ; Aliyu and Tijjani, ; Akinlo and Lawal, ). Ogundipe et al .…”
Section: Empirical Literaturementioning
confidence: 99%
“…(), for example, investigated the effect of Naira devaluation on Nigerian trade balance and found that devaluation deteriorates trade balance in the long run while in the short run devaluation does not affect trade balance. On the contrary, Igue and Ogunleye () analyse the effect of exchange rate depreciation on trade balance in Nigeria using a vector error correction modelling approach. Their findings showed that currency depreciation in Nigeria improves trade balance in the long run since the Marshall–Lerner condition was satisfied.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Though Jibrilla and Shehu (2015) found bidirectional causal relationship between changes in exchange rate and balance of trade, they think depreciation of naira does little to improve Nigeria trade balance. Most recent academic researches on Nigeria exchange rate regimes (Shehu 2010, Umoru and Oseme 2013, Igue and Ogunleye 2014, Jibrilla and Shehu 2015 must have contributed to the existing literature but their approaches could not be considered to be robust. Besides, the sharp drop of naira against dollar as envisage in Fig 1 represent an obvious uncertainty at this period which could cause adverse consequences in Nigeria's external businesses.…”
mentioning
confidence: 99%
“…However, Shahbaz et al (2012), Cao-Alvira (2014), andBaek (2013), Narayan (2006), Bahmani-Oskooee and Wang (2006), conclude for the J-curve hypothesis there is not much support found. The long-run currency depreciation improves the TB and Bahmani-Oskooee and Zhang (2014), Igue and Ogunleye (2014), Iqbal et al (2015), Hsing (2009) andOgutu (2014) argued about it. Whereas, Wang et al(2012) and Datta (2014) found there is no significant impact of depreciation on the TB, therefore, the Marshall-Lerner condition is not satisfied.…”
Section: Literature Reviewmentioning
confidence: 99%